Scaling up Business Plans in Tajikistan: a qualitative study of the history, barriers, facilitators and lessons learnt - Sarah S Werner; Gulara Afandiyeva; Gulzira Karimova; Sabine Kiefer; Nasrullo Abdujabborov; Muazamma Dzhamalova; Ilhom Bandaev; Helen Prytherch (Taylor & Francis Group, 2021)
Background To improve health planning at primary health care (PHC) level, Business Plans were introduced in Tajikistan by the Enhancing Primary Health Care (EPHC) Services Project. Objective To describe the history and process of implementation of Business Plans and to identify barriers, facilitators and lessons learnt from scaling up Business Plans. Methods Set in a qualitative research design, we conducted a desk review of project and official documents and seventeen semi-structured interviews with key stakeholders at national and sub-national levels between May and July 2020. We used an interview guide informed by the ExpandNet/WHO framework and analyzed the data following a content analysis approach facilitated by MAXQDA. Results With the participation of various user organizations and resource teams and through a variety of strategic scale-up choices, Business Plans have been scaled up from a vertical pilot project to institutionalized health management tools covering 45% of Tajikistan's PHC facilities. The most prominent facilitators for scaling up Business Plans were the institutionalization and integration of the tool into the Tajik health system, the close collaboration with Community Health Teams (CHTs), the high acceptance of the tool among the users, the advocacy through champions and policy-makers and the large dissemination network. The most outstanding barriers to scaling up Business Plans were insufficient financial or human resources, general weaknesses in health governance, the lack of a strategic scale-up plan and strategic decisions, the lack of motivation or overall vision to implement Business Plans at a large scale and difficulties in donor coordination. Conclusion To ensure the continuity of scaling up Business Plans, developing a scale-up strategy, strengthening cross-sectoral collaboration and participation during scaling up, and capacitating the user organizations of Business Plans are important next steps to ensure the sustainability and effectiveness of Business Plans in the future.